2003
DOI: 10.1021/la026970c
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Fluid Extraction of a Nonionic Surfactant Template from SBA-15 Materials and Consequences on the Porous Structure

Abstract: SBA-15 mesoporous materials were synthesized using the method reported by Zhao et al. Surfactant was removed from as-made materials by means of different techniques: thermal treatment under air atmosphere, solvent washing at different temperatures, and supercritical CO2 extraction in the presence and absence of cosolvents. The structure of resulting materials was characterized using conventional techniques: nitrogen and argon adsorption measurements, powder X-ray diffraction (XRD), thermogravimetric analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
2
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(111 citation statements)
references
References 40 publications
4
101
2
4
Order By: Relevance
“…In this context, alcohols derived from biomass, like methanol [4], ethanol [3,5], or glycerol [6][7][8] may also be reformed to generate hydrogen, turning reforming into a zero net carbon emissions process. and tailored particle morphology [31]. Large surface area and mesoporous structure of the support have been demonstrated to play an important role in improving Ni dispersion and in suppressing Ni sintering [19,32].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, alcohols derived from biomass, like methanol [4], ethanol [3,5], or glycerol [6][7][8] may also be reformed to generate hydrogen, turning reforming into a zero net carbon emissions process. and tailored particle morphology [31]. Large surface area and mesoporous structure of the support have been demonstrated to play an important role in improving Ni dispersion and in suppressing Ni sintering [19,32].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers [23][24][25] have recently exploited sc-CO 2 in the post synthesis treatment of mesoporous silica. They reported that modified CO 2 could be used to extract the surfactant template from the uncalcined mesoporous silica thus facilitating in the recycling of the surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…A slight hysteresis loop and sharp adsorption step at relative pressures around 0.4-0.6 identify the characteristics of this isotherm 38,39 and the sharpness of the adsorption branches indicates narrow pore size distribution. 40 In Figure 2(a), the slope of the isotherm after the low-pressure adsorption step is lower for Fe loaded SBA-15-SO 3 H than that of pure SBA-15-SO 3 H, corresponding to a lower area of the mesopore surface.…”
Section: Resultsmentioning
confidence: 97%